Brain anatomy of autism spectrum disorders II. Focus on amygdala. (2nd July 2013) - Bellani, M.; Calderoni, S.; Muratori, F.; Brambilla, P.
Abstract : This brief review encompasses the key findings of structural Magnetic Resonance Imaging (sMRI) research on amygdala volume in autism spectrum disorders (ASD). We also highlight the possible correlation between the autistic behavioural phenotype and amygdala alteration.